Peran UMKM Abon Ikan Roa dalam Meningkatkan Ekonomi Masyarakat Desa di Desa Limboro - Nurul Chaeriah; Nur Hilal; Fadila Almahdali (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
This research aims to determine and analyze the role of MSMEs in improving the economy of village communities in Limboro village. As for the usefulness of research (1). Theoretically useful for the author, it is hoped that this research can be an example for future researchers, especially for researchers who discuss the role of Abon Roa Fish MSMEs in improving the economy of village communities in Limboro Village. The type of research used is qualitative research with a descriptive approach. The data collection techniques used were interviews, observation, documentation. The results of this research show that the role of MSMEs has a significant influence on the economy of village communities.